The impact of plant-rich diets on sleep: a mini-review - Polianovskaia, Anastasiia; Jonelis, Michelle; Cheung, Joseph (Frontiers in Nutrition, 2024)
Plant-rich diets (PRDs), also referred to as plant based diets, have been shown to have beneficial effects on various chronic diseases and all-cause mortality. However, limited data are available on the effect of such diets on sleep and sleep disorders. In this review article, we explore existing evidence and potential mechanisms by which PRDs may impact sleep and sleepiness. High-fat diets are associated with drowsiness, while fiber-rich diets improve sleep quality. Anti-inflammatory diets may benefit patients with sleep disturbances, and diets rich in tryptophan and serotonin precursors may improve sleep quality. Isoflavones and polyphenols present in PRDs may also have a positive impact on sleep. Furthermore, diets rich in plants may reduce the risk of obstructive sleep apnea and associated daytime sleepiness. Overall, the current knowledge about PRDs in sleep and sleep disorders is limited, and further research is needed to explore the potential advantages of this dietary approach in sleep disorders.